EFEKTIVITAS PELAKSANAAN PEMBELAJARAN MATEMATIKA ANAK USIA DINI DENGAN MENGGUNAKAN ALAT PERMAINAN EDUKATIF DI TK ULIL ALBAB: Evi Wahyu Ningsih - Evi Wahyu Ningsih (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This research was conducted to determine the thinking ability of children in learning by making educational games effective. The early period of development to improve children's thinking skills since children aged 0-6 years, this period is often referred to as the Golden Age. According to Howard Gardener intelligence is divided into 9, one of the nine intelligences is multiple intelligences. There are many kinds of stimuli to improve the ability of children's cognitive intelligence in the early stages of development, especially by making educational game tools effective as learning media. Educational game tools are everything that can be used as a means of learning and is believed to be able to develop and optimize all children's abilities.